Analysis of the InsCor Score as a Predictor of Mortality in Patients Undergoing Coronary Artery Bypass Grafting - Félix,Iuri Ferreira (2021)
Abstract Introduction: Risk scores are important tools for predicting adverse events in cardiac surgery, but their accuracy varies when applied to different populations. The objective of this study is to evaluate the performance of the Brazilian score InsCor as a predictor of mortality after coronary artery bypass grafting (CABG) compared to the European System for Cardiac Operative Risk Evaluation (EuroSCORE) and Society of Thoracic Surgeons (STS) scores. Methods: This is an observational and retrospective study, with patients undergoing surgical myocardial revascularization in a cardiology hospital in Salvador (Bahia, Brazil), between 2010 and 2015. InsCor, STS, and EuroSCORE were compared for accuracy in predicting mortality within 30 days after surgery. Discrimination capacity of models was assessed using areas under receiver operating characteristic (ROC) curves. Significance level was 5%. Results: Four hundred sixty-one patients were evaluated (mean age 63 [± 8.6] years, 77% men). Thirty-day mortality was 2.6%. InsCor classified 88, 210, and 163 patients as having low, medium, and high risk of death, respectively. According to EuroSCORE and STS, 379 and 430 patients were classified as having low risk and 77 and 29 as medium risk, respectively. Area under the ROC curve was 0.734 (P=0.002) for InsCor, 0.615 (P=0.027) for EuroSCORE, and 0.623 (P=0.033) for STS. ROC curve of InsCor maintained statistical significance after adjustment for other models. Conclusion: The InsCor score, derived from a Brazilian sample, showed good predictive accuracy of death up to 30 days in patients undergoing CABG in relation to STS and EuroSCORE scores.